CONGENITAL ARTERIO-VENOUS MALFORMATION OF OPTIC NERVE HEAD- A RARE CASE - Vikas Sharma; Ankuj Tinna; Vikas Ambiya; Atul K Singh; Ritesh Waghray (Indonesian Vitreoretinal Society, 2022)
Introduction: Retinal arterio-venous malformations (AVMs) are rare, congenital, high-flow congenital developmental vascular anomalies without intervening capillary bed also known as racemose angioma, They are unilateral, nonhereditary lesions located anywhere in retina and may involve optic nerve. Case report: A 55 year old male was found to have abnormal congenital arterio-venous malformation over optic nerve head in his left eye, as an incidental clinical finding. He had reported for his routine fundus examination due to diabetes. He had no other relevant systemic findings. Further follow up was advised to see the progression of the lesion and structural damage to optic nerve. Discussion: The typical clinical picture, fluorescein angiogram findings, normal MRI brain and orbits, and normal base line blood investigations all points in favour of a congenital arterio-venous malformation. Conclusion: Arterio- venous malformations of Optic nerve head are very rare to find as compared to retinal malformations. This is the first such case report from India.